Book Review: Stoyanova, J. (2021) Problemi na psiholingvistikata [Problems of Psycholinguistics]. Sofia University Press - Kyuchukov, Hristo (East European Journal of Psycholinguistics, 2023)
Juliana Stojanova’s main scientific interest is the acquisition of Bulgarian as a first language – with an emphasis on the early stages, and this is well shown in her last monograph published in 2021 by the Sofia University Press.The content of the proposed monograph follows the topic of the course in psycholinguistics, which the author offers as a part of the mandatory curriculum of bachelor’s and master’s students in the “Speech Therapy” degree program and as an elective course for bachelors and masters of philology at Sofia University “St. Kliment Ohridski”. The course has been repeatedly updated to reflect not only the latest developments in psycholinguistics around the world but also the author’s own research in the acquisition of the Bulgarian language. Thus, the monograph turns from a textbook for students and doctoral students in the humanities engaged in the scientific field of psycholinguistics into a guide for all interested in the issues involved.The first part of the book (Chapters 1-3) discusses topics from general psycholinguistics. The second part, dedicated to developmental psycholinguistics (Chapters 4 to 19), describes and analyses the early acquisition of Bulgarian. This part is based on the research of language ontogenesis, which the book’s author has been conducting for about 35 years.Chapter 1 is an introduction to the main problems in psycholinguistics. For psycholinguistics, language is not only an abstract symbolic system but also a mental construct related to memory, thinking, communication, and socio-cultural activities. The most important moments in the history of psycholinguistics are traced. Some theoretical issues which have been discussed since the 50s are presented: redundancy as a property of all natural languages, the frequency of language entities and the experiments for eliciting verbal associations. Attention is paid to memory and the biological foundations of language.Chapters 2 and 3 briefly outline (based on the example of Bulgarian) the most essential characteristics of language units and structures (phonology, morphology, lexis, semantics, syntax, discourse and text) to help readers who do not have philological education to understand the content of native speakers’ language competence. The linguistic perspective is closely intertwined with the psycholinguistic one. The chapters overview the most influential theories on the organisation of the mental lexicon and lexical access, some sentence analysis models, the role of inferences, the scheme and scenario in the processing of discourse information, and, finally, the speech production hypotheses. Chapter 4 begins with an introduction to the problems of developmental psycholinguistics, raising the main theoretical and methodological issues that aim to explain the processes of language acquisition in early childhood.Chapter 5 is dedicated to the pre-linguistic development, which prepares the beginning of speech in the second year of children’s life: it describes the perception of speech, the appearance of babbling, the communicative and the cognitive development.Chapter 6 considers the early stages of language acquisition defined according to the number of words in children’s utterances – one-word-, two-word-, and three-word-stage. In Chapter 7, multi-word combinations in children’s speech production are analysed. Special attention is paid to the omission of grammatical words and morphemes – a phenomenon known as telegraphic speech. This Chapter also deals with the individual variations between children according to the rate (early vs. late talkers) and acquisition style (referential vs. expressive style).The emphasis in Chapter 8 is on the forms and structures specific for the Bulgarian Child Directed Speech, and the role these linguistic means play in promoting language development.Chapter 9 begins with the presentation of some theoretical approaches to the mastering of phonological contrasts, the transition between babbling and the first words, and the representation of words in mental lexicon. This Chapter provides detailed information about the development of the Bulgarian phonemic system: the acquisition of segmental and supra-segmental structure of Bulgarian words, as well as the interrelationship between phonology, morpho-phonemic alternations and derivational morphology in the ontogeny of language.Chapter 10 is devoted to the mastery of vocabulary. The connection between words and concepts, the formation of the early vocabulary, the cases of meaning discrepancy between the standard and children’s words, and the creation of occasionalisms are the main topics discussed in this Chapter.The early development of Bulgarian morphology is traced in Chapters 11 to 14. The mastery of nouns, adjectives, and numerals with their respective grammatical categories for gender, number, and definiteness, as well as the appearance of vocatives (by nouns) and comparative forms (by adjectives), is considered in detail in Chapter 11. Chapter 12 analyses the development of different types of pronouns and the problem of mastering the deictic category of person.Chapter 13 regards the development of verb conjugation, the acquisition of the Bulgarian temporal-aspectual system and the difficulties in mastering the deictic notion of time. It also traces the appearance of non-witness forms, reflexive verbs, and imperatives.The acquisition of grammatical words (adverbs, prepositions, conjunctions, particles) is studied in Chapter 14. It also addresses the problem of overgeneralisation.The mastery of the Bulgarian clause is outlined in Chapter 15. Different ways of expressing syntactic dependence in children’s utterances are delineated: gender and number agreement within the NP, agreement in person and number within the VP, prepositional relations, apposition, case marking in some pronouns, and word order rules.Chapter 16 discusses the process of adding complexity within the clauses: marking of negation, use of reflexives, passives, and impersonal constructions.The development of phrasal and sentential coordination, as well as the process of acquisition of different types of complex sentences, are considered in Chapter 17. The first steps in creating discourse competence are set in the same Chapter.Chapter 18 is devoted to communicative-pragmatic development, describing the mastery of basic speech acts and their expression through indicative, imperative, permissive and interrogative utterances. This Chapter also sheds light on some socialisation aspects through language up to the age of three.The last Chapter discusses one of the most important theoretical questions in psycholinguistics: the role metalinguistic knowledge plays in language development. The Bulgarian data on early language awareness confirm that metalinguistic competence as part of the feedback and control system develops simultaneously with language competence.Like any science, psycholinguistics does not provide ultimate answers to any issues it deals with. It only sets a broad scientific field – still relatively unexplored.The monograph may interest students, doctoral students and specialists in the humanities (philologists, psychologists, speech therapists, pedagogues) who have to do with psycholinguistics, and especially those who are engaged in language development. The book is also a valuable read for people specialising in human medicine. Parents who are looking for answers to questions about their children’s mastery of Bulgarian can also find something for themselves in this book.